Assessing Competition Policy on Economic Development - Oré, Tilsa (Economia, 2013)
Implementation of competition policies is one of the most recommended strategies to developing countries as a tool for achieving economic development. Using a panel dataset of over 100 countries and 7 years (from 2005-2011), I estimate the effect of competition on economic development, and also determine which of the comprehensive policy factors are the most relevant for increasing competition. A fixed effects instrumental variable approach is used.I find that competition intensity positively impacts economic development. The estimate is highly significant when effectiveness of antimonopoly policy and squared years of experience handling competition law are used as instruments for competition intensity. Political stability is shown to be a determinant for higher achievement in development. Macroeconomic environment and financial market development are also significant factors that contribute to higher economic development. Less developed countries should work intensively to improve their institutional quality and implement pro-competitive policies that are not only related to competition laws.